A generalized and mode-adaptive approach to the power flow analysis of the isolated hybrid AC/DC microgrids - Xiao, Yu (2019)
Hybrid AC/DC microgrids (HMG) are emerging as an attracting method for integrating AC/DC distributed energy resources (DERs). In the isolated hybrid AC/DC microgrid (IHMG), the key problem is how to balance power variation and regulate voltage and frequency. Various energy storage systems (ESS) and interlinking converter (IC) technologies are viable for this application. The present study proposes a novel unified power flow (PF) model which can be applied to compare and analyze the practical operation modes of the IHMG and, further, to evaluate and compare the abilities of the ESS with different connection topologies and ICs with different control approaches to maintain the voltage and frequency stability of the IHMG. Five operation modes of the IHMG are defined and explained. Then, a set of generic PF equations are derived. Moreover, three binary matrices are applied as input parameters of the unified power equations. These matrices enable a single operation mode of the IHMG at a time to be constructed in the power equation. Finally, the accuracy and effectiveness of the proposed scheme are verified against the time domain simulation result. The quasi-steady-state behaviors of multi-DC subgrids IHMG in different modes after a range of load fluctuation are investigated. The results show that the use of multiple grid-forming units in the AC and DC subgrids, when IC adopted normalized.